Kolumb rosyjskiej prowincji. O Podróży do Kazania, Wiatki i Orenburga Maksima Niewzorowa - Dąbrowska, Magdalena (Przegląd Rusycystyczny, 2007)
КОЛУМБ РУССКОЙ ПРОВИНЦИИ. О ПУТЕШЕСТВИИ В КАЗАНЬ, ВЯТКУ И ОРЕНБУРГ МАКСИМА НЕВЗОРОВА Резюме Провинциальная Россия — крупное литературно-геoграфическое открытие XVIII века. Об этом свидетельствует Путешествие в Казань, Вятку и Оренбург... (1803), сентиментальное путешествие Максима Ивановича Невзорова (1762/1763–1827). Ав-тор приводит в нем исторические (взятие Иваном Грозным Казани, 1552 г.), а также географические, социологические и этнографические сведения. COLUMBUS OF THE RUSSIAN PROVINCE. ON JOURNEY TO KAZAN, VIATKA AND ORENBURG BY MAXIM NEVZOROV Summary The provincial Russia is a great geographic and literary discovery of 18th century. This is refl ected by Journey to Kazan, Viatka and Orenburg... (1803) being a sentimental journey of Maxim Nevzorov (1762/1763–1827). The writer provides there both historical information (capture of Kazan by Ivan IV in 1552), and also geographic, ethnographic and sociologic information.